2020
DOI: 10.1101/2020.05.19.105445
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical And Analytical Performance Of An Automated Serological Test That Identifies S1/S2 Neutralizing IgG In Covid-19 Patients Semiquantitatively

Abstract: word count: 246 20 Text word count: 3188 21 22 4 ABSTRACT 23BACKGROUND. In the Covid-19 pandemic, highly selective serological testing is 24 essential to define exposure to SARS-CoV-2 virus. Many tests have been developed, 25 yet with variable speed to first result, and of unknown quality, particularly when 26 considering the prediction of neutralizing capacity. 27 OBJECTIVES/METHODS. The LIAISON ® SARS-CoV-2 S1/S2 IgG assay was designed 28 to measure antibodies against the SARS-CoV-2 native S1/S2 protei… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 22 publications
3
51
0
6
Order By: Relevance
“…Manufacturers' sensitivity estimates ranged from 96·8% to 100% on samples taken at least 14 days post symptom onset or RT-PCR, and specificity estimates ranged from 98·5% to 99·8% on pre-pandemic samples ( appendix p 14 ). 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18…”
Section: Methodsmentioning
confidence: 99%
“…Manufacturers' sensitivity estimates ranged from 96·8% to 100% on samples taken at least 14 days post symptom onset or RT-PCR, and specificity estimates ranged from 98·5% to 99·8% on pre-pandemic samples ( appendix p 14 ). 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18…”
Section: Methodsmentioning
confidence: 99%
“…For instance, the LIAISON SARS-CoV-2 S1/S2 IgG assay claims high agreement with neutralizing antibodies. However, the cutoff titer used for the neutralizing assay was 1:40; far below that recommended by FDA for convalescent plasma therapy (13). If neutralizing antibodies >1:256 are required for protection, then commercial assays at the current cutoffs may have limited utility for identifying patients with protective antibodies; with NPA between 18-40% for the assays tested in this study.…”
Section: Discussionmentioning
confidence: 80%
“…Tang 4 Despite widespread interest in neutralizing antibodies, methods for their detection and quantification are relatively low-throughput and limited to Biosafety Level 3-equipped research laboratories. While high-throughput methods have emerged, most rely on recombinant Vesicular Stomatitis Viruses (VSV) engineered to express a portion of the SARS-CoV-2 viral spike protein, and their subsequent entry into cell lines (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…With 1 100% PNA and 100% PPA in the convalescent group, this study describes a more favorable 1 diagnostic accuracy. One of the studies provided the median positive quantitative results for 1 comparison, which ranged from 8-96.3 AU/mL, with 96.3 AU/mL representing their most 1 acutely ill subjects [11]. In comparison, the median positive result in this study was 190 AU/mL, 1 which may suggest our high PPA is a consequence of high patient acuity.…”
Section: Diagnostic Accuracymentioning
confidence: 63%
“…Two peer-reviewed articles and three studies released as pre-prints specifically reported on the 1 accuracy of the DiaSorin SARS-CoV-2 serologic assay in comparison to PCR, with a range of 1 96.8-100% for specificity and 77.8-95.7% for sensitivity in convalescent patients [8][9][10][11][12]. With 1 100% PNA and 100% PPA in the convalescent group, this study describes a more favorable 1 diagnostic accuracy.…”
Section: Diagnostic Accuracymentioning
confidence: 99%